The Relationship between Mansoura City Customers’ Perception of Restaurant Innovativeness and their Advocacy: The Mediating Role of Customer Engagement and The Moderating Role of Openness to Experience in the Light of COVID-19 Crisis - khashan, Mohamed (The Arab Journal of Administration, 2023)
The spread of the new Coronavirus “COVID-19” has enforced a major challenge for the service sector, especially the restaurant sector in recent times, which entails the need for service providers to search for innovative solutions to get out of this crisis. The previous researchers point out that innovation is considered one of the basic ways to deal with crises and promote positive customer behaviours. Thus, this current paper investigates how customer perception of restaurant innovativeness and customer engagement stimulate the rates of restaurants customers' advocacy in Mansoura city. Data were collected from 483 restaurants’ customers. Partial least squares structural equation modelling (PLS–SEM) was employed to test the hypotheses. The findings confirmed that customer perception of restaurant innovativeness significantly impacted customer engagement and customers advocacy. In addition, customer engagement positively influenced customers advocacy. Moreover, the results showed that customer engagement mediated the relationship between customer perception of restaurant innovativeness and customers advocacy. Furthermore, a customer’s openness to experience moderated the relationship between customer perception of restaurant innovativeness and both customer engagement and customer advocacy. Finally, some theoretical and managerial implications of these findings are discussed.